Critical Shear Stress for Erosion of Sand-Mud Mixtures and Pure Mud - Chen, Dake; Zheng, Jinhai; Zhang, Chi; Guan, Dawei; Li, Yuan; Wang, Yigang (Frontiers in Marine Science, 2021)
The erosion threshold of sand-mud mixtures is investigated by analyzing the momentum balance of a sand particle or a mud parcel in the mixture bed surface, and a formula for the critical shear stress of sand-mud mixtures is developed, which also applies for pure sand and mud. The developed formula suggests that the variation of the critical shear stress of sand-mud mixtures over mud content is mainly caused by the varying dry bulk density of the mud component in the mixture. The developed formula reproduces well the variation of the critical shear stress of sand-mud mixtures over mud content and can predict the critical shear stress of both sand-mud mixtures and pure mud in the process of consolidation. The developed formula promises to be convenient for application by relating the critical shear stress to mud content and the dry bulk density of sediment.